Engineering vulnerability evaluation of building structures in coastal areas considering the effects of corrosion - Chi, Xiaona; Xu, Anna; Liu, Yajie; Lun, Peiyuan (Frontiers in Materials, 2023)
Chloride-induced corrosion is an important factor affecting the durability of building structures in coastal areas, which will cause serious deterioration of reinforced concrete (RC) structure and lead to structural failure. However, chloride-induced corrosion is a slow process, which accompanies the whole process of the service life of building structures, and there are many factors that affect the service life of building structure, such as building structure location, structural design, drug management and other factors. This paper was carried out to conduct service life prediction of building structures due to chloride-induced corrosion and service life evaluation of building structures based on the concept of engineering vulnerability. First, the model of corrosion initiation of reinforcement, along with the consequent concrete cover cracking were investigated and proposed. Second, according to the characteristics of building structure and corrosion, the evaluation index system of engineering vulnerability is determined, and the evaluation method of engineering vulnerability considering corrosion is established based on AHP method and fuzzy comprehensive evaluation method; Finally, A case study of a pharmaceutical factory structure in a coastal city, the feasibility of the assessment method considering corrosion effect is verified.